Manifestations of Arabic Language Creativity (A study in Building and Meaning) - Mohamed Ibrahim Hassan Othman; Mohamad Zhafri Mohammad Nazmi; Ibrahim Youssef Abdelhamid; Ummu-Hani Abas (Human Resource Management Academic Research Society, 2024)
Indexed by ERA